(untitled) (The Pakistan Development Review, 2010)
The transition from General Sales Tax (GST) to Reformed General Sales Tax (RGST) has become an intricate and controversial topic for no particular reason. Let me start the discussion by acknowledging that RGST is not a new tax as generally perceived, rather it is the old GST which when fully implemented would be a sufficiently broadened and extended version of the existing GST. The changes in the existing GST would include withdrawal of many of the exemptions and concessions that have been granted over time, gradual abolition of the zero-rating of domestic sales while maintaining zerorating of the export sector, and extension of the existing GST to services that are currently outside the tax net. Thus, those who are opposing RGST believing it to be a new tax are required to be properly educated by the Sales Tax and the Taxpayers’ Education and Facilitation wings of the Federal Board of Revenue (FBR).